The influence of environment and mathematical learning styles on students' GPA through independent learning as an intervening variable - Ekowati, Christine Krisnandari; Madu, Aleksius; Nenohai, Juliana MH; Wangge, Magdalena (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2022)
This study aims to analyze the effect directly or indirectly between learning styles and the learning environment through independent learning on students' cumulative grade point average in the Mathematics Education Study Program, FKIP Undana. The type of research is quantitative research, with the research population being all active students in the Mathematics Education Study Program. The sample taken was 95 people. The samples were based on the Slovin formula with an error of 5%. Data was collected through questionnaires regarding the learning environment, learning styles, learning independence, and GPA. The data collected was then analyzed by path analysis. From the results of the data analysis, it was concluded that 1) there is a significant direct effect between learning styles on student learning independence; 2) there is a significant direct effect between the learning environment on student learning independence; 3) there is no significant direct effect between learning styles on students' GPA; 4) there is a significant direct effect between the learning environment on the student's GPA; 5) there is a significant direct effect between learning independence on the student GPA; 6) there is a significant direct effect between learning styles through independent learning on the student's GPA; 7) there is a significant direct effect between the learning environment through independent learning on the student's GPA. Overall, it can be concluded that there is a significant influence between the environment and learning styles through independent learning on student GPA.